2015
DOI: 10.1186/s40824-015-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro characterizations of porous carboxymethyl cellulose-poly(ethylene oxide) hydrogel film

Abstract: BackgroundCellulose and its derivatives such as carboxymethyl cellulose (CMC) have been employed as a biomaterial for their diverse applications such as tissue engineering, drug delivery and other medical materials. Porosity of the scaffolds has advantages in their applications to tissue engineering such as more cell adhesion and migration leading to better tissue regeneration. After synthesis of CMC-poly(ethylene oxide) (PEO) hydrogel by mixing the solutions of both CMC-acrylate and PEO-hexa-thiols, fabricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Usually, the D band is less active and G band is highly active in few-layered GR than multi layered GR sheets. The 2D bands of were observed at 2726cm −1 and 2724 cm −1 on GR and GR-CMF composite, is due to the two phonon lattice vibrational process on GR sheets [33]. Peak intensity ratio (I2D/IG) of the 2D and G bands of GR and GR-CMF was found as 0.92 and 0.91.…”
Section: Characterizationsmentioning
confidence: 85%
See 1 more Smart Citation
“…Usually, the D band is less active and G band is highly active in few-layered GR than multi layered GR sheets. The 2D bands of were observed at 2726cm −1 and 2724 cm −1 on GR and GR-CMF composite, is due to the two phonon lattice vibrational process on GR sheets [33]. Peak intensity ratio (I2D/IG) of the 2D and G bands of GR and GR-CMF was found as 0.92 and 0.91.…”
Section: Characterizationsmentioning
confidence: 85%
“…3B, the Raman spectra of GR and GR-CMF exhibits a strong G band at 1592 and 1591 cm −1 , and due to the in-plane vibrational modes of sp 2 hybridized carbon atoms on GR [25]. The less intense D band at 1888 and 1387 cm −1 , is ascribed to the vibrations of sp 3 carbon atoms of disordered GR and vibrations of sp 2 carbon atom domains of graphite [33]. Usually, the D band is less active and G band is highly active in few-layered GR than multi layered GR sheets.…”
Section: Characterizationsmentioning
confidence: 95%
“…Their findings, that the expression of this protein varied as a function of cell culture duration, demonstrated that the expression of this membrane protein can serve as a potential marker to investigate cell adhesion in vitro . Typically, the morphology of cells is considered to consist of a spherical shape before adhesion and changes to one of a polygonal or spindle‐like shape after adhering to a surface . However, the double lipid bilayer of the plasma membrane will enable it to flow with the cytoplasm when cells adhere to a surface in order to enhance the cell‐surface contacts .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the morphology of cells is considered to consist of a spherical shape before adhesion and changes to one of a polygonal or spindle-like shape after adhering to a surface. [42][43][44] However, the double lipid bilayer of the plasma membrane will enable it to flow with the cytoplasm when cells adhere to a surface in order to enhance the cell-surface contacts. 45 Given the presence of many adhesion molecules, such as ICAM-1or VCAM-1, which are anchored to the plasma membrane, changes in their expression levels during different phases of the cell adhesion process, not only indicate their participation in regulating the cell adhesion but can also serve as biomarkers of cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in preparation of scaffolds for tissue engineering, these enzymes have been incorporated in bacterial cellulose sheets [114]. Other approaches how to achieve and control the cellulose degradability were its esterification, that is formation of carboxymethylcellulose, which was then susceptible to degradation by esterases [115], acetylation, that is the formation of cellulose acetate, and its further mixing with another polysaccharide, pullulan, in various ratios [116]. Cellulose is also susceptible to hydrolysis by acids and, to a lesser extent, by alkalis (for a review, see [113]).…”
Section: Nanofibers In Skin Tissue Engineeringmentioning
confidence: 99%